2005
DOI: 10.1590/s0034-72992005000600014
|View full text |Cite
|
Sign up to set email alerts
|

Quantas manobras são necessárias para abolir o nistagmo na vertigem posicional paroxística benigna?

Abstract: OBJETIVO: Avaliar o número de manobras necessárias para abolir o nistagmo posicional em pacientes com Vertigem Posicional Paroxística Benigna e verificar possíveis influências do substrato fisiopatológico e/ou canal semicircular acometido. FORMA DE ESTUDO: clínico prospectivo com coorte transversal. MATERIAL E MÉTODO: Sessenta pacientes com Vertigem Posicional Paroxística Benigna foram tratados por meio das manobras de reposicionamento de estatocônios, repetidas semanalmente até a abolição do nistagmo. A Análi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
1
10
1
6
Order By: Relevance
“…The age ranged from 21 to 82 years, similar to that in other published papers. 2,7,20,21 The mean number of maneuvers needed to abolish positioning nystagmus was 2.3. This finding is similar to that in another study in which the mean number of required maneuvers per patient was 2.1.…”
Section: Discussionmentioning
confidence: 99%
“…The age ranged from 21 to 82 years, similar to that in other published papers. 2,7,20,21 The mean number of maneuvers needed to abolish positioning nystagmus was 2.3. This finding is similar to that in another study in which the mean number of required maneuvers per patient was 2.1.…”
Section: Discussionmentioning
confidence: 99%
“…17 The efficacy of Epley's maneuver in the treatment of BPPV patients has been underlined in the literature. [16][17][20][21]26,28,[30][31][32][33][34][35]42,[43][44][45] Only a few authors with smaller series compared to this series have investigated Epley's maneuver in patients diagnosed as having BPPV associated with Ménière's disease. Two patients remained with positional vertigo and four patients remained with nystagmus as evidenced by the Dix-Hallpike test.46 Elimination of positional nystagmus with the persistence of dizziness or mild positional unbalance was seen in 32.1% of the affected labyrinths.…”
Section: Discussionmentioning
confidence: 99%
“…Based on two class i studies, three class ii, four metanalysis and one systematic review, Fife et al 18 classified the maneuver as "Level A recommendation", in other words, treatment is effective and safe, and it should be offered to the patients of all ages with posterior canal BppV. korn et al 25 and dorigueto et al 26 studied the number of maneuvers which must be used to treat BppV and concluded that repeated maneuvers in the same session seem to be more efficient, and even more necessary when one is dealing with cupulolithiasis. it was only in one of the studies 19 hereby analyzed, that it was not possible to identify a specific number or a protocol for such, and the Cr repetition must be determined by symptom severity, if persistent, by the professional's evaluation and its successful treatment with the maneuver.…”
Section: Canal Repositioning Maneuvermentioning
confidence: 99%